Foreign direct investment, financial development, export performance and economic growth in selected transition economies - Rakhimova, Irina (2013)
The purpose of this study is twofold. The first objective is to investigate the nature of relationship between FDI and export in selected transition economies of Former Soviet Union. Specifically, the aim is to test whether they are substitutes or complements. The second objective is to test empirically if financial sector development has any effect in mediating the positive effect of FDI on growth. Employing the panel data on 12 transition economies over the years 1993-2010 and using Pooled OLS, Fixed and Random effect estimation methods, the results show that there is a substitution effect between FDI and exports. This implies that increase in FDI will reduce export. This finding is valid for all estimation techniques. To test the second objective on the possible role played by financial market development in mediating the impact of FDI on output growth, a panel of 12 countries of Former Soviet Union is selected. Using data over the period 1997-2010 and Pooled OLS, Fixed and Random effect estimation methods, the results show that financial market development in these economies is an important pre-condition for them to reap the positive spillover effects from MNCs presence. The result also indicates that the direct effect of FDI on the host economies is negative. The evidence of substitution effect of FDI on export performance in FSU countries suggests a possible “crowding out” effect of foreign capital inflows on domestic firms, probably exporters. It also indicates that the motive of foreign entry is not an export, but the size of domestic market. In addition, it is found that better developed financial markets can boost the effect of FDI in FSU economies. The findings of this study recommend following policy implications such as improving macroeconomic and political stability, developing FDI-welcoming strategies and providing favorable investment climate for foreign investors.